Hungarian Monitoring, 20 April 1990 . [Magyar rádiófigyelő], 1990. április 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Lithuanian embargo - Preparations for Pope John Paul II's visit to Czechoslovakia - Lech Wałęsa's speech at the Solidarity congress Domestic Affairs: - Proposal to shorten military service - Miklós Németh meets the Hungarian IMF representative in the Parliament - Live TV broadcast of the first session of the new Parliament - Coalition talks - Soviet troop withdrawals to be accelerated - A military airplane crashed near Ajka - South African Republic Embassy opened in Budapest - Buenos Aires representative office of the World Federation of Transylvanians calls on the Democratic Alliance of Hungarians in Romania (RMDSZ) to fight for the freedom of Romania Economy: - Agreement with the World Bank Külpolitika: - Litván embargó - II. János Pál csehszlovák látogatásának előkészületei - Walesa felszólalt a Szolidaritás kongresszusán Belpolitika: - Javaslat a sorkatonai szolgálat csökkentésére - Németh Miklós a parlamentben fogadta az IMF magyar képviselőjét - Élő televíziós közvetítés az új Országgyűlés első üléséről - Koalíciós tárgyalások - Felgyorsítják a szovjet csapatok kivonulását - Lezuhant egy katonai repülőgép Ajka közelében - Megnyílt a Dél-afrikai Köztársaság állandó képviselete - Az Erdélyi Világszövetség Buenos Aires-i képviselete felszólítja az RMDSZ-t, hogy küzdjön Románia szabadságáért Gazdaság: - Megállapodás a Világbankkal